2000
DOI: 10.1051/parasite/2000072103
|View full text |Cite
|
Sign up to set email alerts
|

In vivoantileishmanial action of Ir-(COD)-pentamidine tetraphenylborate onLeishmania donovaniandLeishmania majormouse models

Abstract: Summary:lr-(COD)-pentamidine tetraphenylborate which has previously been studied on promastigote forms of Leishmania, was investigated for its antileishmanial properties compared with pentamidine used as reference compound. In vitro, the iridium complex had the same IC 50 value on intracellular forms of Leishmania as pentamidine (15 µM). In vivo, the compound could not be injected intravenously due to the DMSO excipient so that the treatments were performed intraperitoneally or subcutaneously. On the L. donova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…In our present TEM analysis, all reversed amidines and, to a lesser extent, the diguanidine induced marked and frequent alterations in the nuclei and mitochondria of both amastigotes and trypomastigotes. These ultrastructural alterations corroborate the findings from previous reports of studies with pentamidine and its analogues and their effectiveness for the in vitro treatment of L. amazonensis (5), Leishmania tropica (13), Leishmania major (11), and T. cruzi (7), as well as the in vivo treatment of L. donovani and L. major in mouse models (16), suggesting that these dicationic compounds have a common mechanism of action, at least in part. However, since aromatic diamidines have also been localized within non-DNA-containing cytoplasmic organelles such as acidocalcisomes in African trypanosomes (17), the possible involvement of the latter compartments in the mechanism of action of diamidines upon T. cruzi must be considered and represents an interesting matter, which is currently under investigation.…”
Section: Vol 51 2007supporting
confidence: 80%
“…In our present TEM analysis, all reversed amidines and, to a lesser extent, the diguanidine induced marked and frequent alterations in the nuclei and mitochondria of both amastigotes and trypomastigotes. These ultrastructural alterations corroborate the findings from previous reports of studies with pentamidine and its analogues and their effectiveness for the in vitro treatment of L. amazonensis (5), Leishmania tropica (13), Leishmania major (11), and T. cruzi (7), as well as the in vivo treatment of L. donovani and L. major in mouse models (16), suggesting that these dicationic compounds have a common mechanism of action, at least in part. However, since aromatic diamidines have also been localized within non-DNA-containing cytoplasmic organelles such as acidocalcisomes in African trypanosomes (17), the possible involvement of the latter compartments in the mechanism of action of diamidines upon T. cruzi must be considered and represents an interesting matter, which is currently under investigation.…”
Section: Vol 51 2007supporting
confidence: 80%
“…justifies the screening of new compounds. Some organometallic and coordination complexes of iridium, rhodium and platinum and zinc sulfate have been tested against the leishmania parasite [62][63][64][65][66][67][68][69][70][71][72]. Also, some metallointercalators of DNA based on platinum, copper and silver have been evaluated and have shown remarkable antileishmanial activity [73].…”
Section: Gold Complexes As Potential Anti-leishmaniasis Agentsmentioning
confidence: 99%
“…In T. cruzi, some of the new compounds (classified as reversed amidines) presented a high level of activity against amastigotes and trypomastigotes both in vivo and in vitro [18][19][20][21][22][23][24][25][26]. Ultrastructural analysis showed that the different aromatic diamines displayed similar effects in T. brucei, T cruzi and Leishmania, characterized by the presence of swollen mitochondria presenting low electron-density structures, fragmentation of the membrane and crista and mitochondrial disruption [12,13,18,20,23,24,[27][28][29][30][31][32].…”
Section: Mitochondriamentioning
confidence: 92%